Mitochondrial complex I in the post-ischemic heart: reperfusion-mediated oxidative injury and protein cysteine sulfonation. (August 2018) - Kang, Patrick T.; Chen, Chwen-Lih; Lin, Paul; Zhang, Liwen; Zweier, Jay L.; Chen, Yeong-Renn
Abstract: A serious consequence of ischemia-reperfusion injury (I/R) is oxidative damage leading to mitochondrial dysfunction. Such I/R-induced mitochondrial dysfunction is observed as impaired state 3 respiration and overproduction of O2 − . The cascading ROS can propagate cysteine oxidation on mitochondrial complex I and add insult to injury. Herein we employed LC-MS/MS to identify protein sulfonation of complex I in mitochondria from the infarct region of rat hearts subjected to 30-min of coronary ligation and 24-h of reperfusion in vivo as well as the mitochondria of sham controls. Mitochondrial preparations from the I/R regions had enhanced sulfonation levels on the cysteine ligands of iron‑sulfur clusters, including N3 (C425 ), N1b (C92 ), N4 (C226 ), N2 (C158 /C188 ), and N1a (C134 /C139 ). The 4Fe-4S centers of N3, N1b, N4, and N2 are key redox-active components of complex I, thus sulfonation of metal-binding sites impaired the main electron transfer pathway. The binuclear N1a has a very low redox potential and an antioxidative function. Increased C134 /C139 sulfonation by I/R impaired the N1a cluster, potentially contributing to overall O2 − generation by the FMN moiety of complex I. MS analysis also revealed I/R-mediated increased sulfonation at the core subunits of 51 kDa (C125, C187, C206, C238, C255, C286 ), 75 kDa (C367, C554, C564, C727 ), 49 kDa (C146, C326, C347 ), and PSST (C188 ). These results were consistent with the consensus indicating that 51 kDa and 75 kDa are two of major subunits hosting regulatory thiols, and their enhanced sulfonation by I/R predisposed the myocardium to further oxidant stress with impaired ubiquinone reduction. MS analysis further showed I/R-mediated enhanced sulfonation at the supernumerary subunits of 42 kDa (C67, C112, C183, C253 ), 15 kDa (C43 ), and 13 kDa (C79 ). The 42 kDa protein is metazoan-specific, which was reported to stabilize mammalian complex I. C43 of the 15 kDa subunit forms an intramolecular disulfide bond with C56, which was reported to stabilize complex I structure. C79 of the 13 kDa subunit is involved in Zn 2+ -binding, which was reported functionally important for complex I assembly. C79 sulfonation by I/R was found to impair Zn 2+ -binding. No significant enhancement of protein sulfonation was observed in mitochondrial complex I from the rat heart subjected to 30-min ischemia alone in vivo despite a decreased state 3 respiration, suggesting that the physiologic conditions of hyperoxygenation during reperfusion mediated an increase in complex I sulfonation and oxidative injury. In conclusion, sulfonation of specific cysteines of complex I mediates I/R-induced mitochondrial dysfunction via impaired ETC activity, increasing O2 − production, and mediating redox dysfunction of complex I. Graphical abstract: Highlights: I/R propagates complex I sulfonation and adds insult to mitochondrial injury. Reperfusion mediates oxidative injury of complex I with cysteine sulfonation. Cysteine sulfonation of complex I impairs its main electron transfer pathway. Cysteine sulfonation of complex I predisposes myocardium more oxidized. Cysteine sulfonation of complex I impairs its structural integrity.